Qualitative process evaluation of an Australian alcohol media literacy study: recommendations for designing culturally responsive school-based programs. (December 2017) - Gordon, Chloe; Kervin, Lisa; Jones, Sandra; Howard, Steven
Abstract Background Alcohol media literacy programs seek to mitigate the potentially harmful effects of alcohol advertising on children's drinking intentions and behaviours through equipping them with skills to challenge media messages. In order for such programs to be effective, the teaching and learning experiences must be tailored to their specific cultural context. Media in the Spotlight is an alcohol media literacy program aimed at 9 to 12 year old Australian children. This study evaluates the process and implementation of the program, outlining the factors that facilitated and inhibited implementation. From this evaluation, a pedagogical framework has been developed for health professionals implementing culturally responsive programs in school settings. Methods Process measures included: semi-structured interviews with teachers before and after the program was implemented (n = 11 interviews), program evaluation questionnaires completed by children (n = 166), lesson observations completed by teachers (n = 35 observations), and reflective journal entries completed by the researcher (n = 44 entries). A thematic analysis approach was used to analyse all of the data sets using NVivo. Inductive coding was used, whereby the findings were derived from the research objectives and multiple readings and interpretations of the data. Results Five key pedagogical considerations were identified that facilitated implementation. These were: connecting to the students' life worlds to achieve cultural significance; empowering students with real-world skills to ensure relevance; ensuring programs are well structured with strong connections to the school curriculum; creating developmentally appropriate activities while providing a range of assessment opportunities; and including hands-on and interactive activities to promote student engagement. Three potential inhibitors to implementing the alcohol media literacy program in upper-elementary school classrooms were identified. These included topic sensitivities, classroom management challenges, and fitting new programs into already busy school schedules. Conclusion Overall, the program content and individual lessons were well received by the teachers and students. The lessons learned from the development, implementation and evaluation of this program can provide health professionals with key pedagogical strategies for designing culturally responsive educational programs. Culturally responsive programs are critical for ensuring interventions are effective for their specific context.